Estimating Industrial Natural Gas Demand Elasticities in Selected OECD Countries - Rajabi, Mona Mashhadi; Mousavi, Mirhossein (Energy Economics Letters, 2019)
This study aims to estimate industrial natural gas demand in 15 selected OECD countries over the period of 1991 to 2016, within the framework of dynamic panel data model. The long-run income and own price and cross-price elasticities of natural gas in industry sector were computed by using fully modified OLS and dynamic OLS approaches as they have taken care of endogeneity by adding leads and lags (DOLS) or nonparametric approach to deal with serial correlation (FMOLS) in the presence or absence of cointegration. The results indicated that in FMOLS approach income elasticity spans from 0.08 to 0.21 and price elasticity was ranged between -0.05 to -0.07 (respectively in model with constant &trend and constant only). So demand is inelastic to price and income both. While in DOLS approach income elasticity was equal 0.63 and 1.15 and price elasticity was -0.14 and -0.51 in models with constant only as well as model with constant & trend respectively. Due to the price inelasticity of natural gas in the industrial sector, changing the price of natural gas or other substitutes does not lead to dipping the consumption and CO2 emission and levying taxes on natural gas price or other substitutes will not change the consumption habit in industry sector.